Agronomic and Physicochemical Properties Facilitating the Synchronization of Grain Yield and the Overall Palatability of Japonica Rice in East China - Huanhe Wei; Jialin Ge; Xubin Zhang; Wang Zhu; Yinglong Chen; Tianyao Meng; Qigen Dai (Agriculture, 2022)
Understanding the agronomic and physicochemical characteristics related to grain yield and grain quality is an ongoing hotspot. In 2018 and 2019, high-yielding rice with good palatability (HYGP), high-yielding rice with poor palatability (HYPP), and low-yielding rice with good palatability (LYGP) were grown in paddy fields to explore the main traits underlying the better grain yield and overall palatability of HYGP. HYGP and HYPP demonstrated a 18.1–20.7% higher grain yield (p < 0.05) than LYGP; HYGP and LYGP gave an overall palatability from 75.2 to 77.0, higher (p < 0.05) than HYPP. The higher grain yield of HYGP compared to that of LYGP resulted from a larger sink size because of the spikelets per panicle and the higher total shoot biomass weight (p < 0.05). HYGP exhibited more (p < 0.05) panicles per m2 but lower spikelets per panicle and 1000-grain weight than HYPP and maintained a similar grain yield to HYPP. Compared with HYPP and LYGP, HYGP exhibited more (p < 0.05) biomass accumulation from heading to maturity, supported by the higher leaf area index, post-heading leaf photosynthetic rate, and SPAD values. HYGP had higher (p < 0.05) adenosine diphosphate glucose pyrophosphorylase and starch branching enzyme activities at the middle and late grain-filling stages than HYPP and LYGP. HYGP and LYGP had a lower (p < 0.05) chalky area, chalky degree, amylose content, setback, grain protein content, and prolamin content than HYPP, while it had a higher (p < 0.05) gel consistency, breakdown, and ratio of glutelin content to prolamin content. Our results suggested that optimized yield components, more biomass accumulation through improved leaf photosynthetic capacities, a lower amylose content with coordinated enzyme activities involved in starch synthesis, and a lower grain protein content with a better composition were the main traits facilitating the better grain yield and overall palatability of rice in east China.